The orientable genus of the join of a cycle and a complete graph - Ma, Dengju (Ars mathematica contemporanea, 2019)
Naj bosta ?$m$? in ?$n$? dve celi števili. V članku pokažemo, da je orientabilni rod spoja cikla ?$C_m$? in polnega grafa ?$K_n$? enak ?$\lceil \frac{(m - 2)(n - 2)} { 4} \rceil$? če, če je ?$n = 4$? in ?$m ≥ 12$?, ali če je ?$n ≥ 5$? in ?$m ≥ 6n - 13$?.
Keywords: join of two graphs; orientabilni rod grafa; orientable genus of a graph; ploskev; spoj dveh grafov; surface